Mothers Working during Preschool Years and Child Skills. Does Income Compensate? - Cheti Nicoletti; Kjell G. Salvanes; Emma Tominey (Institute of Labor Economics (IZA), 2020)
Increasing mothers' labour supply in a child's preschool years can cause a reduction in time investments that lead to a negative direct effect on mid-childhood and teenage outcomes. But as mothers' work hours increase, income will rise. We ask whether income can compensate for the negative effect of hours by adopting a novel mediation analysis that exploits exogenous variation in both mothers' hours and family income in pre-school years. As expected we find a negative direct effect of an increase in mother's work hours on child test scores at age 11 and 15. However, income fully compensates for this negative direct effect. This is true for the full sample of children, for boys and girls and for children in households whose mother has a low and high level of education.
Keywords: I22; I24; 330; child development; test scores; parental investments